Efeito agudo de saltos intermitentes na arquitetura muscular do Vasto Lateral em atletas de voleibol - Marinho e Lima, K. M.; dos Santos Valente, A. M.; da Silva Avancini, C.; Fernandes de Oliveira, L. (Revista Brasileira de Ciência e Movimento, 2015)
Increased pennation angle of the muscle fibers during contraction causes a reduced muscle force generation. The aim of this study was to investigate the relationship between the pennation angle of the vastus lateralis muscle (VL) with the performance of an intermittent vertical jumps test. We tested a group of 18 male athletes of the Brazilian Army Confederation of Volleyball. Two longitudinal images of the VL, at 50% of thigh length were acquired with a B-mode ultrasound. Soon after, subjects performed a Counter Movement Jump test to evaluate the maximum vertical jump height. The intermittent vertical jumps test comprised four sets of 15 s maximum jumps. Immediately after, the two images of the pennation angle were again obtained in the same region. Two pennation angle measurements were made in each image, totaling eight measurements per individual. The results of this study showed that there was a significant reduction of the jumps heights (35.77 ± 4.67 cm; 31.94 ± 4.51 cm; 27.04 ± 3.93 cm and 22.60 ± 3 66 cm intervals for 0-15 s, 15-30 s, 30-45 s and 45-60 s, respectively). The VL pennation angle did not present a significant difference before and after the test (12.72 ± 2.26 ° and 13.71 ± 3.40º respectively). The Pearson correlation between the pennation angle measurements before and after the intermittent test and among the heights in all intervals were weak (0.034<r<0.253) and not significant. We conclude that the fall of the test performance of intermittent jumps can not be associated with altered pennation angle of VL fibers. Future studies monitoring other variables of the muscle architecture as fiber length and also the tendon stiffness, may elucidate the role of these mechanical factors in the decrease of intermittent jumps heights.